Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, Profitabilitas dan Likuiditas terhadap Ketepatan Waktu Penyampaian Laporan Keuangan pada Masa Covid-19 - Yustin Tri Ayu Ruliyanti; Oktaviani Ari Wardhaningrum; Nur Hisamuddin (Jurnal Buana Akuntansi, 2023)
The purpose of this research is to be able to analyze various factors that are thought to have an influence on the timeliness of submitting financial statements of companies listed on the Indonesia Stock Exchange during the Covid-19 period. The method used in this research is the quantitative method. Data analysis in this study was assisted using the SPSS 23 application. The sample used in this study was selected through purposive sampling technique using certain criteria. After conducting the sample selection process, 252 data were obtained from 83 companies in the non-primary consumer goods sector. The research data consists of the period 2019-2021. The data analysis technique used is descriptive statistics with logistic regression. The study results show that the size of the company affects the timing of submitting financial statements. Meanwhile, institutional ownership, profitability, and liquidity have no effect on the timeliness of submitting financial statements.